Membumikan Gerakan Peduli Lingkungan Melalui Pengembangan Sikap Askesis Ekologis - I.Y. Kristio Budiasmoro (LPPM Press, 2011)
A caring attitude is a basic need to regenerate ecological ascetic attitude, which willbring a paradigm for the community to be involved in the movement of ‘nata mangsa’. Pan acaring attitude to the environment should be conducted systematically from individuals,households, communities and societies that are supported by the regulation in favor of theenvironmental concerns. As a strategy must promote an interdisciplinary approach in the form ofsynergy between the fields of regulatory, academic and socio-economic sustainability ofcommunities.